Efficacy and Safety of Pairing iStent Inject Trabecular Micro-Bypass and iAccess Precision Blade Goniotomy in Patients with Open-Angle Glaucoma - Mark J. Gallardo; Matthew Porter (Ophthalmology and Therapy, 2023)
Abstract Introduction This study evaluated efficacy and safety of implanting two second-generation trabecular micro-bypass stents (iStent inject/iStent inject W) with phacoemulsification, either with or without iAccess Precision Blade goniotomy, in patients with mild-to-moderate open-angle glaucoma (OAG). Methods This retrospective, non-randomized, unmasked, dual-arm, single-site, multi-surgeon, consecutive case series evaluated all OAG eyes that underwent phacoemulsification and iStent inject implantation either as a dual procedure (group A) or paired with iAccess goniotomy (group B) from July 2020 to May 2022. Effectiveness outcomes analyzed from 1 month onward included intraocular pressure (IOP), proportions of eyes with IOP ≤ 12/≤ 15/≤ 18, proportion medication-free, and medication number. Safety outcomes at all timepoints included adverse events and secondary surgeries. Results In group A, mean IOP reduced from 14.9 ± 3.2 mmHg on 1.22 ± 1.31 mean medications preoperatively (n = 63) to 13.5 ± 2.5 mmHg on 0.24 ± 0.61 medications at month 3 (n = 34; p = 0.048 IOP, p < 0.001 medications). In group B, mean IOP reduced from 16.0 ± 4.2 mmHg on 1.12 ± 1.07 medications preoperatively (n = 93) to 12.2 ± 2.3 mmHg on 0.57 ± 1.27 medications at month 3 (n = 23; p < 0.001 IOP, p = 0.003 medications). From preoperative to 3 months, the percent of eyes with IOP ≤ 12 mmHg remained at 32.4% in group A (p = 1.0) and rose from 21.7% to 60.9% in group B (p = 0.0177); eyes with IOP ≤ 15 mmHg rose from 52.9% to 76.5% in group A (p = 0.0963) and from 43.5% to 91.3% in group B (p = 0.0034). Adjusting for baseline between-group differences, group B had significantly greater postoperative IOP reduction than group A (p = 0.043); medication reductions were similar. Safety was favorable in both groups. Conclusions Phacoemulsification and iStent inject with or without iAccess Precision Blade goniotomy produced clinically meaningful and safe IOP and medication reductions. The paired iStent inject + iAccess + phacoemulsification procedure enabled greater IOP reduction and lower IOP thresholds than iStent inject + phacoemulsification. The study provides some of the first data on this paired approach and on the novel iAccess Precision Blade.